2010
DOI: 10.1210/me.2009-0429
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Transcriptional Control of Progesterone Receptor Gene Expression

Abstract: Estrogen receptor alpha (ERalpha) binds to specific target DNA sequences, estrogen response elements (EREs), to regulate estrogen-responsive gene expression. The progesterone receptor (PR) gene has been used extensively as a marker of estrogen responsiveness. Although we previously identified cis elements within 1 kb of the PR-B transcription start site that are associated with ERalpha and help to confer estrogen responsiveness, the identification of ERalpha binding sites far removed from the transcription sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 59 publications
2
38
1
Order By: Relevance
“…2). Two enhancer sites containing EREs (Enh 1 and Enh 3), all homologous to the enhancer sites characterized by BoneyMontoya et al [40] in the MCF-7 cell line, exhibited E2-increased ERα binding in the VMH and POA ( fig. 4 b).…”
Section: E2 and T 3 Cross-talk In The Recruitment Of Erα And Trα To Tmentioning
confidence: 81%
See 3 more Smart Citations
“…2). Two enhancer sites containing EREs (Enh 1 and Enh 3), all homologous to the enhancer sites characterized by BoneyMontoya et al [40] in the MCF-7 cell line, exhibited E2-increased ERα binding in the VMH and POA ( fig. 4 b).…”
Section: E2 and T 3 Cross-talk In The Recruitment Of Erα And Trα To Tmentioning
confidence: 81%
“…6 a). In the Hypo group, the ability of E2 to induce ERα association to the [40] . Black diamonds denote conserved ERE sites between human and mouse enhancer sequences.…”
Section: The Dynamics Of Erα and Trα Binding To The Oxtr Promoter Arementioning
confidence: 99%
See 2 more Smart Citations
“…Having demonstrated that RvD2 increases ERE-SEAP activity, we then ascertained whether it modulates the transcription of estrogen-responsive genes. Growth regulated by estrogen in breast cancer 1 (GREB1) and progesterone receptor are considered markers of estrogen responsiveness (Rae et al, 2005;Bonéy-Montoya et al, 2010). RvD2 significantly increased GREB1 and progesterone receptor mRNA levels in MCF-7 cells (Fig.…”
Section: Erk1/2 Inhibitors (Pd98059 and Uo126) Or P38mentioning
confidence: 99%